2020
DOI: 10.21037/atm-20-2958
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair and surgical ablation for atrial functional mitral regurgitation

Abstract: Background: This observational study aimed to share our experience in the surgical management of atrial functional mitral regurgitation (AFMR).Methods: We retrospectively identified 82 AFMR patients (63.6±7.7 years) from June 2008 to November 2018 at our institution. Of these patients, 72.0% of them were classified as NYHA functional class III/IV, and all of them had persistent AF. All patients underwent mitral valve (MV) repair, and 52 (63.4%) received concomitant surgical ablation (SA). Patients were followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In conclusion, AFMR is a recently described disease entity with a multifaced pathophysiology. It has been speculated that it may become the most common type of MR in the future, 19 considering the fact that the prevalence of both HFpEF and AF is increasing worldwide, with a threefold rise in prevalence over the past 50 years 39 . Its definition in surgical studies broadly varies, with discordance in the inclusion/exclusion criteria for retrospectively defining AFMR patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, AFMR is a recently described disease entity with a multifaced pathophysiology. It has been speculated that it may become the most common type of MR in the future, 19 considering the fact that the prevalence of both HFpEF and AF is increasing worldwide, with a threefold rise in prevalence over the past 50 years 39 . Its definition in surgical studies broadly varies, with discordance in the inclusion/exclusion criteria for retrospectively defining AFMR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vohra et al 15 Takahashi et al 16 Takahashi et al 17 Sakaguchi et al 7 Kaneyuki et al 18 Chen et al 19 Matsumori et al 14 Balogh et al 20 Tanaka et al 13 Hirji et al 21 Carino et al 22 Inclusion criteria Chronic AF Carpentier Type 2…”
Section: Definition Of Afmr: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…As mentioned above, the freedom from cardiac death rate for the MV repair group was higher than that of the MV replacement group in the long term. However, recurrent MR of a greater than mild-moderate degree has been reported in 20-35% of such patients 2-5 years after the MV repair [6,9,11], which suggest that MV repair is not sufficient for correcting MR in certain patients. Our study showed that the 5-and 10-year rates of recurrent MR were 16.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of the maze procedure in this investigation was higher compared to those of the above-mentioned studies, which may have contributed to the postoperative maintenance of sinus rhythm. Chen et al compared mitral repair with concomitant surgical ablation to isolated mitral repair in treating patients with AFMR [ 15 ]. The results indicated that patients may benefit from a concurrent surgical ablation operation in terms of recurrent MR.…”
Section: Discussionmentioning
confidence: 99%